Optimum Conditions for the Removal of Lead from Aqueous Solution Using Paw-paw Trunk Activated Carbon - N. U. Udeh; B. L. James (American Scientific Research Journal for Engineering, Technology, and Sciences, 2022)
The study investigated the optimum conditions for the removal of lead from aqueous solution using chemically activated pawpaw trunk (UPTAC) with ZnCl2. The design of experiment (DoE) was based on three variables, contact time, adsorbate concentration and adsorbate pH, and a total of 27 experimental runs were used to study the effects of the parameters using the response surface methodology (RSM). Batch adsorption studies on the effects of adsorbent dosage, initial adsorbate concentration, contact time and adsorbate pH were used as variables to obtain the optimum conditions. Results showed that the amount of leads adsorbed was found to vary with adsorbent doses, initial adsorbate concentration, stirring time and adsorbate pH. However, the rate of lead removal increased with smaller adsorbent dosage while the amount adsorbed per unit mass increased with increase in initial lead concentrations. Generally, UPTAC achieved optimum % removal of 99.51% at initial lead concentration of 50mg/l and its removal was pH dependent (pH 6) tending towards neutral. Also, there was increase in adsorption of lead ions with increase in stirring time due to increase in kinetic energy of the metal and UPTAC attained equilibrium in 60mins. Thus, UPTAC could effectively remove lead from aqueous medium using the above optimum conditions.